THE APPLICATION OF MODEL PROBLEM BASED LEARNING (PBL) AGAINST STUDENT RESULTS IN SENIOR HIGH SCHOOL 11 SAMARINDA - Paulina Cerling; Muliati Syam; Muhammad Junus (UNIVERSITAS NEGERI MEDAN, 2020)
This study aims to determine the increase in student learning outcomes of class XI IPA 1 senior high school 11 Samarinda after applying the PBL model to the Static Fluid material and to find out student responses about the application of the PBL model in static fluid learning. The research used One Group Pretest-Posttest Design method on Static Fluid material. The technique used was purposive sampling with the sample of this study were 35 students of class XI IPA 1 senior high school 11 Samarinda. The instruments used were written questions and questionnaires. Based on the results of the study showed that the average N-Gain was 0.69. The results of the t-test calculation showed that a significant level of learning outcomes and students' responses to PBL was in a good category or criteria.